Proposal for the establishment of a permanent Caribbean disaster mitigation organization (INMANEX Inc. OttawaCA, 1992)
Assists the Caribbean Community to prepare a programme document on disaster preparedness and prevention that will lead to the establishment of the Caribbean Disaster Mitigation Organization.
Keywords: DISASTER PREPAREDNESS